Clinico-Biological Aspects of Undernutrition in Diabetic Patients Hospitalized in the Medical Department of the Mali Hospital - Ousmane, Faridatou; Goïta, Yaya; Koné, Amadou; Mariko, Modibo; Traore, Bah; Dramé, Sidiki Ibrahim; Doumbia, Nanko; Fomba, Minkoro; Bissan, Aboubacar Tiétié; Dabo, Abdoulaye; Diallo, Mamadou; Bamba, Oussamatou; et al. (European Journal of Applied Sciences, 2023)
Introduction: Undernutrition is a frequent and often unrecognized pathology in the hospital environment. Its consequences are significant both medically and financially, as it increases hospital length of stay, morbidity and mortality. The aim of this study was to assess the clinical and biological aspects of undernutrition in diabetic patients hospitalized in the medical department of the Mali Hospital. Methodology : A survey was carried out on 65 diabetic patients admitted to hospital between April 5, 2022 and November 4, 2022. The diagnosis of undernutrition was based on the 2021 Haute Autorité de Santé (HAS) diagnostic criteria, and the severity of undernutrition was assessed using the International Obesity Tast Force (IOTF) curves in children (<18 years) and albumin measurement in adult diabetic patients (18 years and over). The survey method consisted in collecting information on the clinical and biological aspects of undernourished diabetic patients. Results : This Study showed that the age of our patients ranged from 7 to 82 years, with an average age of 50.96 ± 22.44 years. Females predominated over males, with 52% and 48% respectively. Type 2 diabetes predominated, with a frequency of 75% versus 25% for type 1 diabetes. The mean albumin level was 26.81 ± 5.53 g/l, with moderate to severe undernutrition at 33.96% and 64.15% respectively. Severe undernutrition was 83%, compared with 17% of moderate undernutrition in diabetic children, according to International Obesity Tast Force (IOTF) curves. The mean BMI was 19.57 ± 4.39 kg/m2. From this study, we could conclude that the decrease in albumin levels was correlated with the high frequency of undernutrition in diabetic patients. It would be interesting to assess the nutritional status of diabetic patients on admission, in order to avoid the morbidity and mortality associated with undernutrition.